2022
DOI: 10.1186/s12977-021-00586-w
|View full text |Cite
|
Sign up to set email alerts
|

HIV-2/SIV Vpx antagonises NF-κB activation by targeting p65

Abstract: Background The NF-κB family of transcription factors and associated signalling pathways are abundant and ubiquitous in human immune responses. Activation of NF-κB transcription factors by viral pathogen-associated molecular patterns, such as viral RNA and DNA, is fundamental to anti-viral innate immune defences and pro-inflammatory cytokine production that steers adaptive immune responses. Diverse non-viral stimuli, such as lipopolysaccharide and cytokines, also activate NF-κB and the same anti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…2C). However, we cannot rule out that Vpx influences other aspects of myeloid cell biology unseen here, which may include alterations in interferon signaling, NF-κB activity, and gene silencing (Chougui et al, 2018;Cingoz, Arnow, Puig Torrents, & Bannert, 2021;Fink et al, 2022;Yurkovetskiy et al, 2018). Nevertheless, genetic modification of MDDCs through lentiviral-mediated gene delivery can be a useful tool for testing hypotheses related to cell activation, virus infection, and cell-cell communication.…”
Section: Understanding Resultsmentioning
confidence: 89%
“…2C). However, we cannot rule out that Vpx influences other aspects of myeloid cell biology unseen here, which may include alterations in interferon signaling, NF-κB activity, and gene silencing (Chougui et al, 2018;Cingoz, Arnow, Puig Torrents, & Bannert, 2021;Fink et al, 2022;Yurkovetskiy et al, 2018). Nevertheless, genetic modification of MDDCs through lentiviral-mediated gene delivery can be a useful tool for testing hypotheses related to cell activation, virus infection, and cell-cell communication.…”
Section: Understanding Resultsmentioning
confidence: 89%
“…Furthermore, NF-κB resulted to be activated in ALS patients and mouse models [ 126 , 127 ] in a mouse model of progranulin ( GRN )-deficient FTD [ 128 ], in PD patients [ 129 ], in HD patients and mouse models [ 130 ]. Moreover, a role of NF-κB signaling was detected in SARS-CoV-2 [ 131 ], HBV [ 132 ], HIV-1/2 [ 133 , 134 ], CVB3 [ 135 ], and HSV-1 [ 136 ] infection.…”
Section: The Role Of Neuroinflammation In Viral Infection and Neurode...mentioning
confidence: 99%
“…The question of how Vpx-coding lentiviruses overcome this effect is under investigation. Some studies have observed that Vpx itself is able to suppress the innate immune antiviral response in monocyte-derived macrophages and monocytic cell lines [ 188 , 189 ]. One proposed mechanism is that Vpx is able to bind to the p65 subunit of NF-κB in order to suppress NF-κB activation [ 189 ].…”
Section: Samhd1 and Host Innate Immunitymentioning
confidence: 99%
“…Some studies have observed that Vpx itself is able to suppress the innate immune antiviral response in monocyte-derived macrophages and monocytic cell lines [ 188 , 189 ]. One proposed mechanism is that Vpx is able to bind to the p65 subunit of NF-κB in order to suppress NF-κB activation [ 189 ]. This antagonism was conserved amongst Vpx proteins from distantly related lentiviruses and Vpr from SIV mon , which has SAMHD1-degradation activity [ 189 ].…”
Section: Samhd1 and Host Innate Immunitymentioning
confidence: 99%
See 1 more Smart Citation